Characteristics of Edible Film Made from Pectin of Papaya Peel - Yuniwaty Halim; Carinna Ruth Darmawan (Reaktor)
Papaya (Carica papaya L.) peel contains a considerable amount of pectin, high molecular weight polysaccharides that can be used in edible film making due to its ability to form gels. However, edible film from pectin usually has poor moisture barrier properties. Therefore, pectin is generally combined with glycerol as plasticizer and starch. This research aimed to utilize pectin from papaya peel with the addition of corn starch in edible film making to determine the characteristics of pectin from papaya peel and the effect of pectin and corn starch concentration on edible film characteristics. Pectin extracted from papaya peel was classified as low methoxyl pectin (LMP). The pectin was then utilized in edible films making together with corn starch addition. Two factors were used in this research, which included pectin amount (0.75 g, 1.0 g, 1.25 g) and corn starch concentration (40%, 50%, 60%, based on pectin). The selected edible films formulation was an edible film made from a pectin amount of 1 g with 50% corn starch (based on pectin weight). This formulation showed low water vapor transmission rate (WVTR) of 3.447±0.270 g.mm/m2/hour, a moderate tensile strength of 1.3121±0.0720 MPa, a moderate elongation percentage of 9.42±0.08%, and a thickness of 0.11±0.01 mm.